Lip Cosmetics – A Formulator (OR) An innovator to Overcome a Challenge in Quest of Research with its Advances - Reddy, V. Sarovar (Asian Journal of Pharmaceutics (AJP), 2024)
Cosmetics which are the Greek origin word have been used by people either knowing or unknowingly in their daily life since B.C for maintaining good hygiene, attraction, and beautifying purpose which from the materials or items available from natural or other forms of sources from nature. Various classifications on the term cosmetic have been emerged on its usage, form, and application available sources. The various types of cosmetics used for hair hair, skin, tooth, etc., are mostly available in the form of solid, liquid, gas and semisolids with various consistencies for longer duration of action and specific area of application. Face cosmetics especially lip cosmetics play a significant role in beautifying the entire human personality in orating the surrounding people on various occasions and in regular life. The lip balms, lip stains, lip liner, lip gloss, lipstick, lip oil, etc. are the lip cosmetics available in the market. To formulate a cosmetic, a great challenging task is to overcome by a researcher or scientist or formulator or innovator because the cost or price of cosmetics is higher than the cost of other needs of humans the product available or manufactured must win the user with its enrichment or articulate in appearance by the customer. The selection of ingredients and the method of preparation and its evaluation play an important role in their future marketed product life in its consistency and utility. All lip cosmetics must be formulated using a sufficient amount of waxes, oils, antioxidants, preservatives, coloring agents, perfumes, moisturizing agents, and other essential ingredients and must be properly evaluated for all tests specified such as test on softening point, melting point, stability study test, freedom from grittiness and greasiness, test on pH, stability test for perfume, test on surface anomalies and solubility, test on breaking point and thixotropy character, test on force of application and skin irritation, lead and other metals limit test, and aging stability test. The marketed products available on lip cosmetics with names of Carmex, Nivea, Blistex, Himalaya lip balm, Maybelline NY Super Stay Matte Ink Liquid, Revlon Ultra HD Matte Lip Mousse, SUGAR Cosmetics Smudge Me Not Liquid Lipstick, Zayn and Myza Liquid Lipstick, FACES Canada Ultime Pro Matte Crayon, Colorbar Sinful Matte Lipstick.